2003
DOI: 10.1152/jn.00342.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Functionally Distinct Synaptic NMDA Receptors in Ventromedial Versus Dorsolateral Striatum

Abstract: N-methyl-D-aspartate receptors (NMDARs) are comprised of different subunits. NR2 subunits confer different pharmacological and biophysical properties to NMDARs. Although NR2B subunit expression is uniform throughout striatum, NR2A subunit expression is greater laterally. Pharmacologically isolated NMDAR-mediated excitatory postsynaptic currents (NMDAR-EPSCs) were elicited using minimal local stimulation and recorded in the whole cell configuration to test the hypothesis that biophysical and pharmacological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 49 publications
9
53
1
Order By: Relevance
“…By extension of previous findings (Chapman et al 2003;Li et al 2003Li et al , 2004, we used P6-8 and ϾP12 mice to examine the properties of NMDA receptors in wild-type MSNs in addition to mice of similar ages that were lacking either the NR2A or the NR2C subunit. Our findings show that the ratio of the NMDA to non-NMDA component of EPSCs decreases with development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By extension of previous findings (Chapman et al 2003;Li et al 2003Li et al , 2004, we used P6-8 and ϾP12 mice to examine the properties of NMDA receptors in wild-type MSNs in addition to mice of similar ages that were lacking either the NR2A or the NR2C subunit. Our findings show that the ratio of the NMDA to non-NMDA component of EPSCs decreases with development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies of functional properties of striatal NMDA receptors at excitatory synapses (Chapman et al 2003;Colwell et al 1998;Wirkner et al 2004) suggest changes occur around the end of the second postnatal week. At this time, rodents undergo major alterations in striatal anatomy and physiology including synapse, dendritic spine formation (Tepper et al 1998) and a shift in synaptic plasticity from long-term potentiation (LTP) to long-term depression (LTD) in the dorsolateral striatum (Partridge et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimeric receptors containing NR1/NR2B have slower offset kinetics than receptors built of NR1/NR2A, whereas triheteromeric receptors containing both NR2A and NR2B subunits are characterized by intermediate properties, such as reduced sensitivity to selective NR2B antagonists but slow offset kinetics dominated by the presence of NR2B subunit (Plant et al, 1997;Vicini et al, 1998;Tovar and Westbrook, 1999). A previous study identified functionally different NMDARs in the ventromedial and the dorsolateral striatum on the basis of their different decay time kinetics (Chapman et al, 2003), related to previously observed regional difference in the expression of NR2A and NR2B subunits (Standaert et al, 1994). Figure 7C shows that decay time kinetics of NMDAR EPSCs recorded at ϩ40 mV in VTA neurons from young rats [postnatal day 21 (P21) to P29] were fitted with the double-exponential equation; to compare decay times between different experimental conditions, we calculated a weighted decay time constant ( w ) derived from the weighted mean of the fast and the slow time constants.…”
Section: Pharmacological and Biophysical Properties Of Cocainepotentimentioning
confidence: 99%
“…Selective medial striatal lesions produce spatial learning deficits (Devan & White, 1999), and medial striatum preferentially receives limbic input (Groenewegen, Vermeulen-Van de Zee, te Kortschot, & Witter, 1987). Also, medial and lateral striatum possess different NMDA systems, suggesting different mechanisms of neuroplasticity (Chapman, Keefe, & Wilcox, 2003). Second, there are two routes by which hippocampal information may impact behavior in an experience-dependent way (Mizumori, Pratt, Cooper, & Guazzelli, 2002) one initially involving striatal circuitry and another passing through cortical circuitry involving the retrosplenial cortex and medial precentral cortex .…”
Section: Implications For Multiple Memory Systems Theorymentioning
confidence: 99%